Analisis Rasio Profitabilitas Dan Aktivitas Sebagai Dasar Penilaian Kinerja Keuangan (Studi Kasus Pt Sariguna Primatirta Tbk Periode 2017 – 2021) - Mariska Oktaviani Wijaya; Hurriyaturrohman Hurriyaturrohman; Muhamad Nur Rizqi (eCo-Fin, 2023)
This study aims to determine and analyze the financial performance of PT Sariguna Primatirta Tbk for the 2017-2021 period which is listed on the Indonesia Stock Exchange (IDX). The research was conducted using Profitability Ratios and Activity Ratios with descriptive analysis research types using quantitative methods. The results of this study show Profitability Ratios with average values which include: Gross Profit Margin 38%, Net Profit Margin 11%, Return On Assets 10%, Return On Equity 10%, and Return On Investment 15%. Gross Profit Margin can be said to be in good condition because it has an average value above industry standards, for Net Profit Margin, Return On Assets, Return On Equity and Return On Investment it can be said to be in unfavorable condition because the average value is still below standard industry. For the results of the Activity Ratio with an average value which includes: Receivable Turnover 18 times indicating good condition because it is above industry standards, Inventory Turnover 6 times, Fixed Assets Turnover 3 times, and Total Assets Turnover 0.86 times which indicates the company's condition is less good because it is still below the average industry standard value.